Multi-scale analysis of the impact of polylactide morphology on gas barrier properties. (13th January 2017) - Fernandes Nassar, Samira; Guinault, Alain; Delpouve, Nicolas; Divry, Véronique; Ducruet, Violette; Sollogoub, Cyrille; Domenek, Sandra
Abstract: Semicrystalline polylactide (PLA) films with controlled morphology were produced by thermal crystallization to optimize the oxygen barrier properties. The crystalline morphology of PLA at the scales of the lamella and the spherulite was investigated and the mobile amorphous phase dynamics were studied. The crystalline morphology had a negligible impact on the oxygen diffusion coefficient. The occurrence of a rigid amorphous fraction (RAF) in the amorphous phase due to its insufficient decoupling from the crystalline phase provided an accelerated pathway for diffusion, though. As a conclusion, for reaching optimal barrier properties, semicrystalline PLA should be pre-nucleated and rapidly crystallized from the glass in the α-polymorph in the aim to reach a high crystallinity degree and decoupling of the amorphous and the crystalline phase. These recommendations can benefit to industry for the optimization of PLA annealing treatments. Graphical abstract: Highlights: Rigid amorphous fraction decreases oxygen barrier properties in PLA. Spherulite size and lamellae thickness do not impact oxygen barrier properties. High barrier properties are obtained by cold crystallization for short time at 130 °C.